The Illusion of Greener Pastures: Violence and Justice for Female Ugandan Migrant Workers in the Middle East (Strathmore Law Journal, 2021)
High levels of unemployment especially among the youth remains one of Uganda’s challenges. About 165,000 Ugandans currently work in the Middle East; some in search of greener pastures through what the labour movement terms as labour expropriation. The Ugandan Government has recognised this expropriation as one providing employment opportunities for young people and good for Uganda’s economy. However, many youth - mostly young women - have fallen prey to violence and abuse meted on them by their employers, including physical and sexual abuse. This article illustrates through real experiences of Ugandan women, the negative consequences of labour expropriation, which have attracted national visibility because of the obvious human rights and gender-based violations that arise especially in the form of violence against women. The article also examines the legal and policy framework relevant to expropriation, including bilateral agreements signed between Uganda and receiving countries in the Middle East. Making reference to interviews with returnees or former domestic workers in the Middle East as well as key informants working in key institutions, this interrogation finds both the laws and structures for protection of young women inadequate in terms of meeting their subjective needs and expectations for protection against violence while working abroad. Going forward, the Ugandan Government should make deliberate efforts at addressing the plight of female migrant workers in the Middle East through strengthening the legal framework and facilitating the Ministry of Gender, Labour and Social Development to undertake stronger monitoring of recruitment agencies, among other initiatives.